2020
DOI: 10.30935/scimath/9549
|View full text |Cite
|
Sign up to set email alerts
|

Measuring the mathematical problem solving and procedural skills of students in an Irish higher education institution – A pilot study

Abstract: In 2010 the Irish second level mathematics curriculum underwent a period of significant change when a new mathematics curriculum was introduced. Some preliminary research has been carried out into the impact, if any, that this mathematics curriculum is having on students mathematics performance which have suggested that students' procedural skills are declining year on year however their problem solving skills may have improved (Treacy and Faulkner 2015). Additional research in this area also highlighted that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(16 citation statements)
references
References 11 publications
1
15
0
Order By: Relevance
“…Treacy and Faulkner (2015) carried out one of the first pieces of research to investigate whether there were any changes in students' mathematical performances after the introduction of PM. Their research examined students' basic mathematical skills on entry to undergraduate education and built on the work of Gill et al (2010) and Faulkner et al (2014Faulkner et al ( , 2020, all of which reported steady declines in students' basic mathematical skills over time. Although Treacy and Faulkner (2015) also found that the decline in students' basic mathematical skills on entry to higher education had continued after the introduction of PM, they outlined an indication that students' problem solving skills had improved over this period of change.…”
Section: Quality and Qualifications Ireland (Qqi) Awards Explainedmentioning
confidence: 99%
See 2 more Smart Citations
“…Treacy and Faulkner (2015) carried out one of the first pieces of research to investigate whether there were any changes in students' mathematical performances after the introduction of PM. Their research examined students' basic mathematical skills on entry to undergraduate education and built on the work of Gill et al (2010) and Faulkner et al (2014Faulkner et al ( , 2020, all of which reported steady declines in students' basic mathematical skills over time. Although Treacy and Faulkner (2015) also found that the decline in students' basic mathematical skills on entry to higher education had continued after the introduction of PM, they outlined an indication that students' problem solving skills had improved over this period of change.…”
Section: Quality and Qualifications Ireland (Qqi) Awards Explainedmentioning
confidence: 99%
“…However, this is not a recently reported issue. The challenges that many students face when trying to apply the mathematics they have engaged with in a formal education setting to a work place setting, or indeed for the benefit of further study of formal mathematics, is something which has been reported in the literature for a long time (Faulkner et al, 2020;Hutton, 1998;Treilibs, 1979).…”
Section: Challenges Surrounding Problem Solving Skills In Mathematicsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, students' lack of knowledge in a particular concept is what happens in most South African schools where rote learning is promoted just for students to pass the tests and examination without conceptual understanding (Mahlaba, 2020). Rote learning generally leads to students experiencing difficulty to apply simple mathematical concepts to applied scenarios (Faulkner, Breen, Prendergast, & Carr, 2020).…”
Section: / 10mentioning
confidence: 99%
“…Both groups, could not use the correct mathematical methods. Research revealed that such errors are due to either students' misunderstanding of mathematics questions or/and difficulty in application of simple mathematical concepts to a new scenario (Faulkner et al, 2020;Fitriani, Turmudi, & Prabawanto, 2018). Such errors can be interpreted as transformation errors.…”
Section: Theme 2: Misunderstanding Of Mathematical Terminologymentioning
confidence: 99%